Pengaruh Penggunaan Media Audiovisual Dalam Pembelajaran Agama Islam di SMP Negeri 1 Sidikalang - Manik, Loli Asmitasari; Lubis, Reskina Cahaya; Bancin, Aisyah (Yayasan Rahmat Islamiyah, 2024)
This study aims to explore the Influence of Audiovisual Media Usage in Islamic Education Learning at SMP Negeri 1 Sidikalang. The research method employed is a case study with participants consisting of teachers and students from SMP Negeri 1 Sidikalang. Data were collected through classroom observations, interviews, and document analysis. The findings indicate that the usage of audiovisual media in Islamic education learning at SMP Negeri 1 Sidikalang has a positive impact on students' understanding, learning motivation, and engagement in the learning process. These findings provide valuable insights for curriculum development and instructional strategies at the secondary school level.